An update on the clinical consequences of polypharmacy in older adults: a narrative review - Wastesson, Jonas W.; Morin, Lucas; Tan, Edwin C.K.; Johnell, Kristina (Expert opinion on drug safety, 2018)
Introduction: Polypharmacy, the use of multiple medications by one individual, is increasingly common among older adults. Caring for the growing number of older people with complex drug regimens and multimorbidity presents an important challenge in the coming years. Areas covered: This article reviews the international trends in the prevalence of polypharmacy, summarizes the results from previous reviews on polypharmacy and negative health outcomes, and updates a previous review on the clinical consequences of polypharmacy by focusing on studies published after 2013. This narrative review, which is based on a literature search in MEDLINE and EMBASE from January 1990 to June 2018, was undertaken to identify relevant articles. Search terms included variations of polypharmacy and multiple medications. Expert opinion: The prevalence of polypharmacy is increasing worldwide. More than half of the older population is exposed to polypharmacy in some settings. Polypharmacy is associated with a broad range of clinical consequences. However, methods to assess the dangers of polypharmacy should be refined. In our opinion, the issue of 'confounding by multimorbidity' has been underestimated and should be better accounted for in future studies. Moreover, researchers should develop more clinically relevant definitions of polypharmacy, including measures of inappropriate or problematic polypharmacy.